2015
DOI: 10.1080/10447318.2014.994193
|View full text |Cite
|
Sign up to set email alerts
|

On the Usability and Effectiveness of Different Interaction Types in Augmented Reality

Abstract: One of the key challenges of augmented reality (AR) interfaces is to design effective hand-based interaction supported by computer vision. Hand-based interaction requires free-hands tracking to support user interaction in AR for which this article presents a novel approach. This approach makes it possible to compare different types of hand-based interaction in AR for navigating using a spatial user interface. Quantitative and qualitative analyses of a study with 25 subjects indicate that tangible interaction i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 35 publications
(61 reference statements)
0
16
0
Order By: Relevance
“…An increasing scholarly intention has been paid to immersive technology such as AR and VR [23]. AR enables users to deal with virtual information which is superimposed on the real world [e.g., 15,47]. VR, in contrast, facilitates a digital created and interactive 3D environment which enables various ways of interaction, collaboration and communication [16,20].…”
Section: Review: Virtual Reality and Immersionmentioning
confidence: 99%
See 2 more Smart Citations
“…An increasing scholarly intention has been paid to immersive technology such as AR and VR [23]. AR enables users to deal with virtual information which is superimposed on the real world [e.g., 15,47]. VR, in contrast, facilitates a digital created and interactive 3D environment which enables various ways of interaction, collaboration and communication [16,20].…”
Section: Review: Virtual Reality and Immersionmentioning
confidence: 99%
“…Researchers have identified sensorimotor contingencies (SC) as a salient system feature of immersive VR [24,30,47,50]. SC describe visual, auditory and haptic feedback, as well as movement tracking [e.g., 15,47]. Since VR facilitates an interactive VE with a high degree of media richness, it is able to cause reactions and behavior of individuals that are similar to those in reality [27,55], such as social behavior [55].…”
Section: Review: Virtual Reality and Immersionmentioning
confidence: 99%
See 1 more Smart Citation
“…To enhance the virtual co-location experience and to facilitate the remote guiding task, more research is needed to explore how to further enhance the communication bandwidth between users. Current research efforts around multimodal interactions combining gestures, audio and annotations , around using physical objects as interaction means (Datcu et al 2015), or around how to provide remote users with a full control of their view, where they are able to zoom in and out, change their point of view as they see fit (as pointed out by Tait and Billinghurst in this special issue) are early steps in this direction.…”
Section: Research Agendamentioning
confidence: 99%
“…Billinghurst and Thomas (2011) also point out that further research on how users can interact within collaborative AR systems is necessary. For example, investigating whether bare hand interaction or interaction with a physical object is more effective in AR (Datcu et al 2015). Recent research has shown that virtual co-location is in fact possible.…”
Section: Introductionmentioning
confidence: 99%